Atomically dispersed cobalt catalyst anchored on nitrogen-doped carbon nanosheets for lithium-oxygen batteries - Wang, Peng; Ren, Yingying; Wang, Rutao; Zhang, Peng; Ding, Mingjie; Li, Caixia; Zhao, Danyang; Qian, Zhao; Zhang, Zhiwei; Zhang, Luyuan; Yin, Longwei (Nature communications, 2020)
Developing single-site catalysts featuring maximum atom utilization efficiency is urgently desired to improve oxidation-reduction efficiency and cycling capability of lithium-oxygen batteries. Here, we report a green method to synthesize isolated cobalt atoms embedded ultrathin nitrogen-rich carbon as a dual-catalyst for lithium-oxygen batteries. The achieved electrode with maximized exposed atomic active sites is beneficial for tailoring formation/decomposition mechanisms of uniformly distributed nano-sized lithium peroxide during oxygen reduction/evolution reactions due to abundant cobalt-nitrogen coordinate catalytic sites, thus demonstrating greatly enhanced redox kinetics and efficiently ameliorated over-potentials. Critically, theoretical simulations disclose that rich cobalt-nitrogen moieties as the driving force centers can drastically enhance the intrinsic affinity of intermediate species and thus fundamentally tune the evolution mechanism of the size and distribution of final lithium peroxide. In the lithium-oxygen battery, the electrode affords remarkably decreased charge/discharge polarization (0.40 V) and long-term cyclability (260 cycles at 400 mA g −1 ). The performance of Li-O 2 batteries is largely determined by the oxygen electrocatalytic reactions at the cathode. Here, the authors report cobalt single-atom catalysts anchored on carbon nanosheets. The design improves oxygen redox kinetics and enables good electrochemical performance.